The idea of war and the problem of its transformation - Panafidin, Igor (Actual Problems of Mind, 2017)
The author considers the classic theory of war by Carl von Clausewitz, as well as the conceptions of modern thinkers M. van Creveld and H. Hofmeister which claim to revise the main ideas of Clausewitz’s theory. The author proposes to devide strictly between the idea of war and war as social practice.